Transient apostle : Paul, travel, and the rhetoric of empire - Luckritz Marquis, Timothy (Synkrisis., 2013)
In a significant reevaluation of the place of St. Paul in the early history of Christianity, this book explores the theme of travel through the surviving correspondence of the Apostle. The author casts Paul's rhetorical strategies against the background of Roman imperial policy, the commerce facilitated by conquest & the knowledge of foreign customs & peoples it allowed.